A extensão em uma universidade tecnológica: docentes como agentes de mudanças - Viviurka, Angela Bernert (2010)
The knowledge produced at university becomes available to society through the university extension. Thus, this dissertation was developed with the purpose of presenting a diagnosis of university extension activities under the perspective of professors from Federal University of Technology - Parana - UTFPR. The study was set against a broad framework based on some authors, with approaches to the role of education and university, with FÁVERO (1980), SILVA (2002) and SANTOS (2005); the use of technology and more specifically, technological education, in REIS (1995) and LIBÂNEO (2001); the question of the importance of identity with BOTOMÉ (2001) and GIDDENS (2002), up to focusing on the extension per se, with GURGEL (1986), TAVARES (1997) and NOGUEIRA (2000) and assign it to a community of practice with WENGER (1998). The methodological approach was based on a qualitative research, an interpretive nature, and quantitative, survey-type. Interviews were conducted with managers to verify their point of views over extension definitions currently applied within UTFPR. Simultaneously, a set of questionnaires to all professors of the UTFPR Campi, located in the cities of Apucarana, Campo Mourão, Cornélio Procópio, Curitiba, Dois Vizinhos, Francisco Beltrão, Londrina, Medianeira, Pato Branco, Ponta Grossa and Toledo was sent by mail. This action allowed to know about the professors’understanding in relation to the extension activities, the way they interact with society, the use of technological resources as well as evaluate the professors’ views in relation to cultural development extension at the university. This dissertation concludes that the extension is not considered minor activity in relation to teaching and research at the university; that the professors do not have clarity about the concept and functions of the university extension at UTFPR and there is need for greater understanding on the identity of this university. As a suggestion from professors, aiming at consolidating the institutionalization of extension activities of UTFPR, the registration and disclosure of extension activities as well as the flexibility of teaching hours along with a scoring mechanism of the curriculum or set of metrics. The implementation of communities of practice in the UTFPR extension would provide the creation of spaces for reflection and for knowledge and experience sharing. The results of this research could contribute to a rethinking of strategies aimed at strengthening the social function of UTFPR for greater involvement of the internal community, as well as the inseparability involving education, research and extension.